Study of biomarkers in the epithelial-mesenchymal transition of triple negative breast cancers and their associations with clinicopathological parameters - Chai, Xiu Hui (2011)
Triple Negative Breast cancer (TNBC) is a newly studied subtype of breast cancer. Existing literature demonstrates that as cancer advances, the tumor cells will undergo epithelial-mesenchymal transition (EMT) to form secondary tumors at distant site. E-cadherin and Vimentin are biomarkers for epithelial and mesenchymal states respectively. β-catenin is involved in maintaining stable epithelial complex with E-cadherin and in signalling pathway implicated in tumorogenesis.